2020
DOI: 10.1108/jica-11-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual framework: factors enabling collaborative healthcare and social services integration

Abstract: PurposeA conceptual framework for collaboratively based integrated health and social care (IHSC) integration is proposed to aid in understanding how to accomplish IHSC.Design/methodology/approachThis model is based on extant literature of successfully IHSC initiatives.FindingsThe model aims to identify enabling integration factors that support collaborative integration efforts between healthcare and social services organizations. These factors include shared goals and vision, culture, leadership, team-based ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(86 citation statements)
references
References 41 publications
(145 reference statements)
12
73
0
Order By: Relevance
“…Some administrators in our study demonstrated the value they placed in primary care engagement through early primary care involvement in system co-design and by encouraging PCPs to lead or co-lead the OHT. Shared leadership has been identified as a core enabling factor for integrated healthcare according to two recent reviews [26,27]. It will be of interest to follow the OHTs over time to observe how PCP involvement will impact the success of the OHT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some administrators in our study demonstrated the value they placed in primary care engagement through early primary care involvement in system co-design and by encouraging PCPs to lead or co-lead the OHT. Shared leadership has been identified as a core enabling factor for integrated healthcare according to two recent reviews [26,27]. It will be of interest to follow the OHTs over time to observe how PCP involvement will impact the success of the OHT.…”
Section: Discussionmentioning
confidence: 99%
“…Administrators struggled with how to adequately compensate PCPs in an equitable way with other OHT partners (e.g., PFAs) and generally seemed unaware of PCPs' concerns around professional autonomy. Adequate compensation has been highlighted in the implementation literature generally, as well as specifically to integrated care, as key to success [26][27][28]. Although the Ministry announced funding for approved teams, at the time of this study, during the formational stage, no funding was provided.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cheng and Catalo model of health care and social services integration helps explain how health care entities and community-based organizations can partner to address these social risk factors (Cheng & Catallo, 2019). Their model defines seven essential factors (Shared Visions & Goals, Leadership, Culture, Team-based Care, Dedicated Resources & Funding, Accountability Agreements, Performance Management, and Information Sharing & Communications) for collaboration between health care and social service organizations, as well as four external domains (Funding Models, Governance Systems, Public Policies, and Community/Geography) that influence these collaborations.…”
Section: Conceptual Frameworkmentioning
confidence: 99%